Penerapan Zonasi Vastu Citra Pada Perancangan Pusat Kesenian Wayang Tradisional Di Bali - Tegar Septian Mboro; Imanuel N. Mbake; I Gusti Ngurah Wiras Hardy (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2025)
Abstract:Traditional Balinese wayang, as a cultural heritage, faces the threat of extinction due to digitalization. This research proposes the design of a Wayang Arts Center in Pantai Lembang, Gianyar, as a medium for preserving the artistic meaning through an architectural metaphor approach, utilizing the natural beach lighting as a visual manifestation of